2016
DOI: 10.14260/jemds/2016/1372
|View full text |Cite
|
Sign up to set email alerts
|

Role of Von Willebrand Factor in Type 2 Diabetes Mellitus Patients

Abstract: BACKGROUNDEndothelial dysfunction is the main cause of morbidity and mortality in diabetic patients. Endothelial dysfunction has been incriminated in the early pathogenesis of atherosclerosis and is considered an early indicator of cardiovascular disease by dysregulation of vascular tone, growth, thrombogenicity, inflammation and the development of both micro-and macro-vascular disease states. Von Willebrand factor is a well-known marker of endothelial dysfunction. The objective of this study is to measure pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 25 publications
(22 reference statements)
0
3
0
Order By: Relevance
“…However, under pathologic conditions, vWF plasma level may be used as a biomarker of endothelial damage and dysfunction, since it is secreted almost only by D r a f t endothelial cells (Frankel et al 2008;Meigs 2010). Previous studies demonstrated increased vWF level in type 2 diabetic patients or in insulin resistance (Frankel et al 2008;Umadevi et al 2016), as well as associated increased risk of cardiovascular diseases with higher levels of vWF in these populations (Frankel et al 2008).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…However, under pathologic conditions, vWF plasma level may be used as a biomarker of endothelial damage and dysfunction, since it is secreted almost only by D r a f t endothelial cells (Frankel et al 2008;Meigs 2010). Previous studies demonstrated increased vWF level in type 2 diabetic patients or in insulin resistance (Frankel et al 2008;Umadevi et al 2016), as well as associated increased risk of cardiovascular diseases with higher levels of vWF in these populations (Frankel et al 2008).…”
Section: Discussionmentioning
confidence: 94%
“…It is known that endothelial dysfunction occures in patients with DM and that it plays important role in the development of atherosclerosis (Umadevi et al 2016). In endothelium damage and dysfunction an increase in the plasma levels of endothelial markers, such as von Willebrand factor (vWF) occurs (Umadevi et al 2016). One of the long-term complications of DM and vasculopathy is diabetic nephropathy (Pop-Busui et al 2010) and hepatopathy (Reid 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Legese et al evaluated the risk of type 2 DM in 424 patients and reported an increased risk in the B blood group and a lower risk in the O blood group; however, the Rh blood group and type 2 DM were not significantly related (5). Increased factor VIII-VWF complex, intercellular adhesion molecule-1(ICAM-1), and tumor necrosis factor-2 (TNF-2) levels in those with B blood group have been associated with a higher risk of DM development in these patients (6,7). Aggarwal et al also found a reduced risk of DM in the O blood group.…”
Section: Discussionmentioning
confidence: 99%